Exploring the challenges of MP3 audio steganography - Atoum, Mohammed Salem; Ibrahimn, Subariah; Sulong, Ghazali; Zeki, Akram M.; Abubakar, Adamu (2014)
This paper presents the issues and challenges faced for steganographic techniques that uses MP3 (Moving Picture Experts Group-1 "MPEG-1" Audio Layer 3) files as the cover or carrier file. The problem of steganographic techniques for MP3 is variety of MP3 states, where it exists at higher or lower bit rates, with higher or lower resulting quality. These have profound effects on strength of techniques that will be used for a different state of MP3 files. Several techniques have already been proposed for embedding data in MP3 files using steganography systems. Unfortunately, there are lacks of general emergence research on the issues and the challenges faced with the MP3 file in terms of steganography. Some techniques for embedding information in MP3 files were reviewed, and recommendations are being proposed for the best strategy of hide information in MP3 files and the possibility of finding other new techniques hiding information in MP3 files